Evaluasi Tata Kelola Teknologi Informasi pada Operasional Sistem KRS Menggunakan Framework COBIT 5 Domain DSS04 (Studi Kasus: Universitas X) - Garet Alfirmansyah; Fachruddin Edi Nugroho Saputro (Universitas Muhammadiyah Klaten, 2026)
The poor process of filling out the Study Plan Card (KRS) indicates systemic IT governance problems in many universities in Indonesia. Problems such as online queues, system errors, schedule conflicts, and high administrative burdens on academic advisors (PA) indicate a failure of information system management. The purpose of this study is to evaluate differences in the operation of the KRS Information System. In addition, this study suggests improvements based on the DSS04 (Management Operations) process domain within the COBIT 5 IT governance framework. A qualitative case study with interviews and document analysis at University “X” was used as the research methodology. The analysis results show five important areas that are not well managed: capacity and performance, operational security, user support, configuration, and incident management. The results produce a DSS04 implementation framework that includes the formation of a special operations team, the implementation of a real-time monitoring dashboard, the preparation of standard operating procedures (SOPs), and a tiered training program. According to the evaluation, the implementation of this framework can reduce KRS system downtime by up to 70%, increase user satisfaction (students and PA lecturers) by 40%, and reduce the average incident resolution time from 48 hours to 4 hours. This study found that a structured IT governance approach through COBIT 5 DSS04 resolves operational technical issues and makes the KRS process more reliable, secure, and user-service-centric. Ultimately, this will help the university achieve its academic goals.